Autonomous Vehicle and Smart Traffic - Ersoy, Sezgin; Waqar, Tayyab (2020)
Long-term forecasting of technology has become extremely difficult due to the rapid realization of any suggested idea. Communication and software technologies can compensate for the problems that may arise during the transition period between idea generation and realization. However, this rapid process can cause problems for the automotive industry and transportation systems.Autonomous vehicles are currently a hot topic within the transportation sector. This development is related to the compatibility of vehicles of the near future with the development of the infrastructure on which these vehicles will be based. There are certain problems regarding the solutions that are currently being worked on, such as how autonomous should vehicles be, their control mechanisms, driving safety, energy requirements, and environmental use. The problem is not just about the design of autonomous vehicles. The user transportation systems of these vehicles also need problem-free solutions. The problem should not only be seen as financial because sociological effects are an important part of this feature.In this book, valuable research on the modeling, systems, transportation, technological necessity, and logistics of autonomous vehicles is presented. The content of the book will help researchers to create ideas for their future studies and to open up the discussion of autonomous vehicles.